Emergent STEM lecturer identities: The shaping effects of EMI in action in an internationalised and Englishised HE context. (July 2021) - Block, David
Abstract: This paper examines the emergent identities of three STEM (science, technology, engineering and mathematics) lecturers, focusing especially on how they construct themselves with regard to their disciplines and how researchers construct them as potential English language teachers. It begins with essential background information before discussing identity as a key construct. The paper then moves to the presentation of a Foucauldian-inflected version of positioning theory which is employed as a means of understanding the construction of English-medium instruction (EMI) STEM lecturer identities. In the second half of the paper, there is a discussion of three case-studies of EMI STEM lecturers, which shows how each orientates to his or her subject discipline, and the prospect of acting, on occasion, as an English language teacher. Specifically, there is a detailed consideration of how EMI lecturers position themselves in their contacts with researchers and in their teaching; how their self-positionings are consistent or not with how researchers position them; and how self-positionings are similar or different across EMI lecturers. The paper ends with a discussion of what conclusions can be drawn from the research findings.